2022
DOI: 10.52082/jssm.2022.426
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Exercise Testing with Elastic Resistance: A New Reproducible Proposal for Determination of Ventilatory Thresholds and Maximum Oxygen Consumption

Abstract: To propose a new Cardiopulmonary Exercise Test with Elastic Resistance (CPxEL) and compare the physiological responses to conventional cardiopulmonary exercise test (CPx) performed on a treadmill. In addition, we tested the reproducibility of the CPxEL. Twenty-four physically active participants completed the CPx (first session) and CPxEL twice (second and third sessions) interspersed by seven days. A treadmill protocol with increments of 1km·h-1 every minute until exhaustion was used in CPx. The CPxEL consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Stavres et al [18] reported that concentric exercise provided greater PEH in healthy young men and women, compared to eccentric exercise, probably due to metabolic stress combined with work. Therefore, it is speculated that the type of effort generated running back and forth performed in EL-HIIT may cause greater vascular shear stress due to increased blood flow toward the active muscle after EL-HIIT vs. HIIT, which has been associated with better vascular adaptations [13,15] and consequently strength-related benefits [16]. More studies should objectively explore the strength component after the different protocols.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stavres et al [18] reported that concentric exercise provided greater PEH in healthy young men and women, compared to eccentric exercise, probably due to metabolic stress combined with work. Therefore, it is speculated that the type of effort generated running back and forth performed in EL-HIIT may cause greater vascular shear stress due to increased blood flow toward the active muscle after EL-HIIT vs. HIIT, which has been associated with better vascular adaptations [13,15] and consequently strength-related benefits [16]. More studies should objectively explore the strength component after the different protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Ventilatory variables and oxygen consumption (VO 2 ) were measured as described in CPET. This test was proposed by Gasparini-Neto et al [16].…”
Section: Elastic Resistance Cardiopulmonary Exercise Test (El-cpet)mentioning
confidence: 99%
See 1 more Smart Citation
“…CPx and HIIT were performed on a motorized treadmill (Inbrasport Super ATL, Porto Alegre, Brazil) with a fixed 1% slope. CPxEL and EL-HIIT were performed on a rubberized mat with an adjustable belt attached to a 2 m elastic tube (Thera Band ® , Akron, OH, USA) [ 20 ]. All participants were instructed to have a light meal at least 2 h before the test and avoid strenuous exercise, caffeinated products, and alcoholic beverages 24 h before the tests and exercise sessions.…”
Section: Methodsmentioning
confidence: 99%
“…However, the exercise prescription proposed by Gasparini-Neto and collaborators was monitored only by the subjective perception of the effort scale [ 17 ]. Considering the need for movement specificity to prescribe exercise with elastic resistance, these same authors proposed an incremental test with reproducible elastic resistance (CPxEL) to determine maximal oxygen consumption and ventilatory thresholds in healthy young individuals [ 20 ]. Based on the CPxEL, it will be possible to prescribe the intensity more accurately for this exercise type.…”
Section: Introductionmentioning
confidence: 99%